Qualitative elemental analysis of farm animals’ milk adopting laser spectroscopic technique - AABDEL–SALAM, Z; EL-SAYED, A (The Indian Journal of Animal Sciences, 2014)
Information about the elements in milk represents a major tool to identify different milk types and their quality. This is because milk constituents of minerals, proteins and fats differ by different mammals and even for different breeds. In the present work, fresh samples of widely consumed farm animals’ milk, namely from buffaloes, camels, sheep and goats were analyzed qualitatively using laser induced breakdown spectroscopy (LIBS) technique. It was focused on calcium, magnesium, iron, sodium, strontium and barium. Molecular bands of CN in the LIBS spectra were used to study the proteins levels in different milk samples. The results revealed that milk samples from different animals could be characterized as completely different combination of the elements constituents were present in magnesium and iron were higher in goat milk compared to the other animals; in addition, the percentage of barium relative to calcium was lower in all milk samples which confirm plant feeding for all studied animals. In general, this work demonstrates the feasibility of using LIBS as a simple, fast and cost effective technique to perform in situ qualitative analysis of milk samples in dairy farms without any need to transport samples to the laboratories.